1989
DOI: 10.1111/j.1600-0528.1989.tb00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic ulcers and pain in adults during orthodontic treatment

Abstract: In the present investigation the frequency of oral ulcers and pain in 79 adults orthodontic patients was recorded. Only four of all patients had never had oral ulceration during treatment, but 83% of the patients characterized the trouble as minor. About 47% of the patients said that ulcers caused by the fixed appliance were the most annoying part of the treatment, and 38% said that activation of the appliance caused the most discomfort. In about 63% of the patients there was less pain when the treatment had l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 9 publications
5
51
0
5
Order By: Relevance
“…12 Other studies related the complaints arising from orthodontic therapy and showed that ulcers were the most annoying treatment factor, cited by 47% of respondents, followed by the discomfort caused by appliance activation, with 38% of complaints. 11 Orthodontics still has few resources for the adequate management of these complications.…”
Section: Resultsmentioning
confidence: 99%
“…12 Other studies related the complaints arising from orthodontic therapy and showed that ulcers were the most annoying treatment factor, cited by 47% of respondents, followed by the discomfort caused by appliance activation, with 38% of complaints. 11 Orthodontics still has few resources for the adequate management of these complications.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming patients do not grind or clench their teeth all night, the time sleeping with the teeth within the freeway-space gives the appliances the opportunity to act more, which may lead to a perception of greater discomfort in the morning. Other investigators (Kvam et al, 1989;Jones and Chan, 1992) found that 22-28 per cent of patients reported sleep disturbances due to pain from orthodontic appliances. In our sample 18 per cent reported being awakened the first night with pain from the appliance.…”
Section: Pain Sitesmentioning
confidence: 99%
“…Several studies have described patients' responses to fixed orthodontic appliances. These .studies report that pain begins a few hours after application of an orthodontic force and lasts approximately 5 days (Jones, 1984;Jones and Richmond, 1985;Sinclair et al, 1986;Feinmann et al, 1987;Kvam et al, 1987Kvam et al, , 1989Ngan et al, 1989;Wilson et al, 1989;Jones and Chan, 1992). There is less unanimity about the question of how fast pain starts and whether or not the force magnitude, the sex and the age of the patient influence the outcome of pain reports.…”
Section: Introductionmentioning
confidence: 99%